Management of learner supervision through principals' control of punctuality in primary schools in Mopani District. - Mbalati, Basani Violet (My University, 2006)
This thesis is a study on the management of learner supervision through principals’ control of punctuality in primary schools in the Mopani District. The study investigated the ways in which primary school principals manage learner supervision through control of punctuality. The investigation has brought to the light what is happening in schools regarding the management of learner supervision through control of punctuality. The literature review highlighted why learner supervision is essential in schools. Particular areas in the school and activities which require supervision were discussed. The relevance of theory to the management of learner supervision was also highlighted. The study also attempted to look at policy initiative with regard to the implementation of management of learner supervision. An attempt was made to integrate some educational policies, laws and regulations with regard to the implementation of learner supervision. The empirical research was done by the questionnaires distributed to the randomly selected schools in Mopani District and the results were discussed. The questionnaires were analysed through tables. The aim was to find out how learner supervision is managed through control of punctuality by principals from learners, educators and principals. Finally, the researcher gave general recommendations for improving the management of learner supervision through control of punctuality.
Thesis (M.Ed.) --University of Limpopo, 2006.
Keywords: Punctuality in schools